A Youth Suicide Prevention Plan for Canada: A Systematic Review of Reviews. (June 2015) - Bennett, Kathryn; Rhodes, Anne E; Duda, Stephanie; Cheung, Amy H; Manassis, Katharina; Links, Paul; Mushquash, Christopher; Braunberger, Peter; Newton, Amanda S; Kutcher, Stanley; Bridge, Jeffrey A; Santos, Robert G; et al.
Objective: We conducted an expedited knowledge synthesis (EKS) to facilitate evidence-informed decision making concerning youth suicide prevention, specifically school-based strategies and nonschool-based interventions designed to prevent repeat attempts. Methods: Systematic review of review methods were applied. Inclusion criteria were as follows: systematic review or meta-analysis; prevention in youth 0 to 24 years; peer-reviewed English literature. Review quality was determined with AMSTAR (a measurement tool to assess systematic reviews). Nominal group methods quantified consensus on recommendations derived from the findings. Results: No included review addressing school-based prevention ( n = 7) reported decreased suicide death rates based on randomized controlled trials (RCTs) or controlled cohort studies (CCSs), but reduced suicide attempts, suicidal ideation, and proxy measures of suicide risk were reported (based on RCTs and CCSs). Included reviews addressing prevention of repeat suicide attempts ( n = 14) found the following: emergency department transition programs may reduce suicide deaths, hospitalizations, and treatment nonadherence (based on RCTs and CCSs); training primary care providers in depression treatment may reduce repeated attempts (based on one RCT); antidepressants may increase short-term suicide risk in some patients (based on RCTs and meta-analyses); this increase is offset by overall population-based reductions in suicide associated with antidepressant treatment of youth depression (based on observational studies); and prevention with psychosocial interventions requires further evaluation. No review addressed sex or gender differences systematically, Aboriginal youth as a special population, harm, or cost-effectiveness. Consensus on 6 recommendations ranged from 73% to 100%. Conclusions: Our EKS facilitates decision maker access to what is known about effective youth suicide prevention interventions. A national research-to-practice network that links researchers and decision makers is recommended to implement and evaluate promising interventions; to eliminate the use of ineffective or harmful interventions; and to clarify prevention intervention effects on death by suicide, suicide attempts, and suicidal ideation. Such a network could position Canada as a leader in youth suicide prevention.